Use of video-recordings of site-based interviews for quality assurance in a study of subjects with schizophrenia and persistent negative symptoms - Targum, Steven D.; Ge, Tingting; Asgharnejad, Mahnaz; Reksoprodjo, Petra; Singh, Jaskaran B.; Murthy, Venkatesha (Schizophrenia research, 2024)
Site-independent ratings derived from audio-digital recordings of site-based interviews are often used for quality assurance monitoring to affirm ratings reliability in CNS clinical trials. The present study of subjects with schizophrenia and persistent negative symptoms used video instead of audio recordings of site-based interviews and thereby facilitated visual observation of the subject by the remote rater. “Paired” site-independent scores of the Positive and Negative Syndrome Scale (PANSS) and Brief Negative Symptom Scale (BNSS) were obtained from video-recordings of site-based interviews. The intraclass correlation between site-based and paired site-independent ratings was r = 0.839 for the total PANSS scores (n = 1006) and r = 0.871 for the total BNSS scores (n = 892); <5 % of paired scores deviated outside the acceptable confidence intervals. Ratings “outliers” were identified and remediated. We examined the pattern of paired scoring deviations for the BNSS, total PANSS, PANSS symptom subscales, and the Marder negative symptom factor. Each metric revealed a bidirectional pattern of scoring deviations such that mean site-based ratings were higher than site-independent ratings when symptom severity was high but lower than site-independent ratings when symptom severity was low. The pattern of bidirectional paired scoring deviations observed in this analysis has previously been noted in paired ratings analyses of subjects experiencing an acute exacerbation of psychosis in schizophrenia and major depressive disorder as well. The bidirectional pattern may reflect inherent differences between live ratings and remotely scored recorded ratings. This analysis affirms the utility of video-recordings of site-based ratings for surveillance in trials with subjects with schizophrenia and persistent negative symptoms.